1999
DOI: 10.1021/jp9833348
|View full text |Cite
|
Sign up to set email alerts
|

Studying Heterogeneous Catalysis by the Scanning Electrochemical Microscope (SECM):  The Reduction of Protons by Methyl Viologen Catalyzed by a Platinum Surface

Abstract: The feedback mode of the scanning electrochemical microscope (SECM) was used for studying a surface-catalyzed electron-transfer reaction. As a model system we examined the reduction of protons by reduced N,N‘-dimethyl-4,4‘-bipyridinum, methyl viologen radical cation, MV+•, catalyzed by a platinum surface. The experimental configuration comprises a biased amalgamated Au ultramicroelectrode (UME) that approaches an unbiased Pt UME substrate of the same radius. MV+• that is electrochemically generated at the amal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 47 publications
5
65
0
Order By: Relevance
“…The RG effect at an unbiased substrate, which has not been considered in any previous SECM study, 21,23,33 was further confirmed by simulating approach curves for probes with different outer diameters (Figure 4a). With b/a = 10, current approach curves change from negative to positive as RG changes from 50 to 1.1.…”
Section: Rg Effect On the Detectable Substrate Sizesupporting
confidence: 56%
“…The RG effect at an unbiased substrate, which has not been considered in any previous SECM study, 21,23,33 was further confirmed by simulating approach curves for probes with different outer diameters (Figure 4a). With b/a = 10, current approach curves change from negative to positive as RG changes from 50 to 1.1.…”
Section: Rg Effect On the Detectable Substrate Sizesupporting
confidence: 56%
“…In the case of the result at shorter distance, it is possible that steady-state [8,36] or transient [5] surface phenomena are responsible for the larger differences observed. The experimental re- sults agreed well, within the experimental error, with the simulated prediction.…”
Section: à11mentioning
confidence: 94%
“…In terms of methodology, this work thus further contributes to a growing body demonstrating that SECM is a powerful tool for the investigation of the catalytic activity of nanostructured interfaces. [7,[44][45][46][47][48][49][50] Moreover, the work provides an impetus for inducing the HER mediated by redox-active solution species.…”
Section: Introductionmentioning
confidence: 99%